Thermal Properties of Soil Samples from Coastal Sand Landform in Ilaje Local Government Area of Ondo State, Nigeria (JOURNAL OF ADVANCES IN PHYSICS, 2016)
This study examines the thermal conductivity of some selected soil samples from coastal sandlandform inIlaje local government area of Ondo State, Nigeria. The soil samples were sieved into different particle sizes; 300 , 425 , 600 , 850 , and 1180 with appropriate mesh and moulded in form of a Lees disc. The thermal conductivity of the samples was determined using parallel plate method. The value of the thermal conductivity increase as the moisture content increaseand decrease with increase in particle sizes for the soil samples. The values of the thermal conductivity obtained rangedbetween 0.3444 and1.8894 . It was noted that the conductivity of the landforms conforms to the range of conductivities of soil required for some specific crops such as maize, cowpea, pineapple, okro and root crops. The results in the research would be useful to soil/building and soil scientists as well as modern mechanized farmers in determined appropriate land forms for agricultural and structural purposes.